The Correlation between Teamwork and Employee’s Productivity - Aldyssa Nurul Kamila Hanifa; RINY JEFRI; Andi Hajar (Ikatan Dosen Katolik Indonesia, 2023)
This research is a quantitative correlational study with pilot design that aims to comprehend correlation between teamwork and employee’s productivity. One of essential things in interpersonal skills at work is Teamwork. Teamwork is a process which gather individuals, ideas, and skills to reach goals. If teamwork is not valued in a workplace, people will frequently work on erroneous tasks and goals, leaving them incomplete. It is essential to cooperate with other co-workers in order to maximize productivity. Employees that are more productive provide several benefits to companies. As a result, increasing employee productivity is crucial. The population in this study is 250 employees, using quota sampling. The correlation design research and the spearman coefficient used in this study to see if there is a relationship between teamwork and employee productivity. This study shows there is relation between teamwork and employee’s productivity at moderate level, 0,592. The data calculated using a statistic application.